Mecanismos para medir las relaciones interpersonales en el cumplimiento de metas del talento humano de la Cooperativa de Ahorro y Crédito unión mercedaria del cantón Latacunga - Lovato Vega, Andrea Fernanda (2015)
The research that we present with the Topic “Mechanisms to improve the interpersonal relationships in the fulfill of goals of human talent at Unión Mercedaria saving and credit Cooperative in Latacunga City” has the purpose to improve interpersonal relationships between employees, the same consists some fundamental categories which are detailed: inquiry of thesis, bibliographic documents, and websites among others. They allowed us to develop this research. At the same time the information of financial institution was studied, which was our study object, methods and research techniques was applied which were used to collect information from the all workers of the cooperative….